Analysis of Suitability of Water Quality Parameters for Vaname Shrimp (Litopenaeus Vannamei) Cultivation in Barombong Village - Ma’sum, Andi Bayani; Jamaluddin, Jamaluddin; Patang, Patang (Agricultural Technology Education Study Program, 2023)
The South Sulawesi region has ideal land resources for aquaculture, such as the coastal area of Barombong village, where land use has not been fully utilized by the local community. Good weather and qualified workers have the potential to develop vaname shrimp aquaculture. Beside as a tourist attaction, the coastal areas can also be utilized for aquaculture. Therefore, the purpose of this study was to analyze the suitability of water quality parameters for vaname shrimp cultivation in Barombong Beach. This study used a quantitative descriptive research with observational methods and water quality measuemeremts covering temperature, brightness, pH, dissolved oxygen, salinity, phosphate, nitrate, ammonia and plankton at three different stations, namely station 1 located near the mouth of the Jeneberang River, station 2 in behind Gor Barombong, and station 3 in the mangrove area. The data analysis technique used is quantitative descriptive analysis and scoring analysis. The results showed that the water quality at Barombong Beach at station 1 with a score of 95.8%, station 2 with a score of 95.8%, and station 3 with a score of 100% is still within the range of water quality standards for the life of white vaname shrimp. and therefore it is suitable for vannamei shrimp (Litopenaeus vannamei) aquaculture.